Dispatching citizens as first responders to out-of-hospital cardiac arrests: a systematic review and meta-analysis. (10th March 2022) - Scquizzato, Tommaso; Belloni, Olivia; Semeraro, Federico; Greif, Robert; Metelmann, Camilla; Landoni, Giovanni; Zangrillo, Alberto
Abstract : Mobile phone technologies to alert citizen first responders to out-of-hospital cardiac arrests (OHCAs) were implemented in numerous countries. This systematic review and meta-analysis aim to investigate whether activating citizen first responders increases bystanders' interventions and improves outcomes. We searched PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials from inception to 24 November 2021, for studies comparing citizen first responders' activation versus standard emergency response in the case of OHCA. The primary outcome was survival at hospital discharge or 30 days. Secondary outcomes were discharge with favourable neurological outcome, bystander-initiated cardiopulmonary resuscitation (CPR), and the use of automated external defibrillators (AEDs) before ambulance arrival. Evidence certainty was evaluated with GRADE. Our search strategy yielded 1215 articles. After screening, we included 10 studies for a total of 23 351 patients. OHCAs for which citizen first responders were activated had higher rates of survival at hospital discharge or 30 days compared with standard emergency response [nine studies; 903/9978 (9.1%) vs. 1104/13 247 (8.3%); odds ratio (OR), 1.45; 95% confidence interval (CI), 1.21–1.74; P < 0.001], return of spontaneous circulation [nine studies; 2575/9169 (28%) vs. 3445/12 607 (27%); OR, 1.40; 95% CI, 1.07–1.81; P = 0.01], bystander-initiated CPR [eight studies; 5876/9074 (65%) vs. 6384/11 970 (53%); OR, 1.75; 95% CI, 1.43–2.15; P < 0.001], and AED use [eight studies; 654/9132 (7.2%) vs. 624/14 848 (4.2%); OR, 1.82; 95% CI, 1.31–2.53; P < 0.001], but similar rates of neurological intact discharge [three studies; 316/2685 (12%) vs. 276/2972 (9.3%); OR, 1.37; 95% CI, 0.81–2.33; P = 0.24]. Alerting citizen first responders to OHCA patients is associated with higher rates of bystander-initiated CPR, use of AED before ambulance arrival, and survival at hospital discharge or 30 days. Abstract :